Asuhan Kebidanan Komprehensif Pada Ny. S Umur 32 Tahun Dengan Kekurangan Energi Kronik (KEK) di BPM Ny. R Wilayah Kerja Puskesmas Bumiayu Kabupaten Brebes Tahun 2023 - Eka Aftri Suryani; Hafsah Hafsah; Rianti Rianti (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Background: The global maternal mortality rate (MMR) in 2022 is 91.46 per 100,000 live births with the cause of death being bleeding while the indirect causes of maternal mortality are during pregnancy wheere many pregnant women experience nutritional problems such as Chornic Energi Deficiency ( CHD) and Nutritional Anemia at 8.43% (WHO, 2022). The maternal mortality rate in ASEAN is 235 per 100,000 live births with the majority of causes of death being bleeding (ASEAN Secretariat, 2022). Until now, the maternal mortality rate in Indonesia alone in 2020 was 91.45/100,000 live births. In 2021, maternal mortality will increase to 305/100,000 live births. Meanwhile, in 2022, the maternal mortality rate will decrease by 230/100,000 live births. Within a period of 3 years, the causes of maternal death included Covid 19, bleeding, hypertension in pregnancy, and heart disease (Ministry of Health of the Republic of Indonesia, 2022). The maternal mortality rate in Central Java in 2020 was 84.6/100,000 live births, in 2021 it will be 199/100,000 live births. In 2022 there will be a decrease to 98.6/100,000 live births, hypertension in pregnancy and bleeding are still the cases of death in that year (Central Health Office, 2022). Brebes Regency shows that the maternal mortality rate in 2020 was 62 cases. In 2021 there were 105 cases and in 2022 there was a decrease to 50 cases with the causes of death being bleeding, hypertension, infection and heart disorders (Brebes District Health Office, 2021) Objective: Reduce maternal and infant morbidity and mortality rates in Brebes Regency, especially the Bumiayu Community Health Center area Conclusion: After providing comprehensive midwifery care to Mrs. S aged 32 years with Chronic Energy Deficiency (KEK) at BPM Mrs. The R working area of the Bumiayu Community Health Center from the third trimester of pregnancy, childbirth, newborns, postpartum and family planning is in good condition.